Upaya-Upaya Extra Effort Dirjend. Pajak Terhadap Optimalisasi Tingkat Kepatuhan Penyampaian SPT Tahunan PPh Wajib Pajak Badan dan Orang Pribadi Tahun 2020 - Sunarmin, Sunarmin -- (Jurnal Pajak Vokasi (JUPASI), 2023)
The contribution of the Directorate General of Taxes' extra efforts toward optimizing the level of compliance in the submission of Annual Income Tax Returns for Corporate and Individual Taxpayers in 2020 is discussed in this Final Project Report. The goal of this final project is to see if the Directorate General of  Taxes   is making  any extra  efforts   to  improve  the  level   of compliance in submitting the Annual Income Tax Return for Corporate and Individual Taxpayers in 2020, given that the COVID-19 pandemic storm is expected to hit Indonesia in that year. The author's observation method is qualitative observation, which is based on document studies, interviews, and informants. According to the author's observations, the Directorate General of Taxes' extra effort towards optimizing the level of compliance in the submission of Annual Income Tax Returns for Corporate and Individual Taxpayers in 2020 has made a significant contribution, such that even during the COVID-19 pandemic, the level of compliance in submitting the Annual Income Tax Return for Corporate and Individual Taxpayers in 2020 has increased due to the intensive efforts made by the Directorate General of Taxes.Laporan Tugas Akhir ini membahas mengenai kontribusi upaya-upaya extra effort yang dilakukan oleh Direktorat Jenderal Pajak terhadap optimalisasi tingkat kepatuhan penyampaian SPT Tahunan PPh Wajib Pajak Badan dan Orang Pribadi di Tahun 2020. Tujuan penulisan ini dilakukan untuk mengetahui adakah kontribusi upaya-upaya extra effort yang dilakukan oleh Direktorat Jenderal Pajak terhadap optimalisasi tingkat kepatuhan penyampaian SPT Tahunan PPh Wajib Pajak Badan dan Orang Pribadi di Tahun 2020, mengingat tahun 2020 badai pandemi COVID-19 sedang melanda Indonesia. Metode   pengamatan yang digunakan oleh penulis adalah pengamatan kualitatif berdasarkan studi dokumen dan wawancara dan informan.Berdasarkan hasil pengamatan penulis upaya- upaya extra effort yang dilakukan oleh Direktorat Jenderal Pajak terhadap optimalisasi tingkat kepatuhan penyampaian SPT Tahunan PPh Wajib Pajak Badan dan Orang Pribadi di Tahun 2020 memiliki kontribusi yang nyata, sehingga meskipun di tengah pandemi COVID-19, tingkat kepatuhan penyampaian SPT Tahunan PPh WP Badan dan Orang Pribadi di tahun 2020 mengalami kenaikan dikarenakan upaya-upaya yang gencar dilakukan oleh Direktorat Jenderal Pajak.